Zinc Finger Proteins in Gastric, Pancreatic, and Prostate Cancers: Molecular Functions, Biomarker Potential, and Therapeutic Opportunities - Beyaz, Seda; Ekşi, Beyza Nur; Öztürk, Hacer Beyza; Büyüksungur, Ayşenur; Aslan, Abdullah (My University, 2025)
Deciphering the molecular mechanisms that drive cancer progression is essential for the development of effective diagnostics and therapeutics. In this study, we systematically examine the structural and functional attributes of Zinc Finger Proteins (ZFPs) and delineate their mechanistic roles in gastric, pancreatic, and prostate cancers, with a particular focus on processes such as epithelial-mesenchymal transition (EMT), DNA damage response (DDR), stemness, and therapeutic resistance. As transcriptional regulators, ZFPs participate in critical cellular processes, including gene expression control, cell proliferation, differentiation, apoptosis, EMT, metastasis, and chemotherapy resistance. By evaluating these roles, the study explores the potential of ZFPs as diagnostic, prognostic, and therapeutic targets in cancers such as gastric, pancreatic, and prostate cancer. ZFPs contribute to key cellular functions, including transcriptional regulation, chromatin remodeling, and cellular differentiation. In oncogenic contexts, they modulate mechanisms like cell cycle control, EMT, metastasis, suppression of apoptosis, inflammation, and drug resistance. These diverse functions highlight ZFPs as promising molecular targets for advancing cancer diagnostics and therapeutics.
Keywords: Apoptosis; Cancer; Biomarker; Transcription factors; Zinc Finger Biology (ZFPs)